The effect of ARIAS learning model on the learning outcomes about continental food processing in Bogor 3 State Vocational Schools from creativity of students - Supari Muslim; Nisa Rahmaniyah Utami; Rita Ismawati; Erina Rahmadyanti; Nita Kusumawati; Ridwan Che Rus (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2019)
This study aims to obtain information about: (1) differences in learning outcomes between students who study using the ARIAS learning model and students who learn using direct learning (DL); (2) differences in learning outcomes between students who have high creativity and students who have low creativity; and (3) whether the relationship between the use of learning models and learning outcomes in continental food processing is influenced by students' creativity. This experimental study was conducted using a 2 x 2 factorial design, with the moderator variable being students' creativity. In the experiment, the separation of the level of student creativity was not carried out significantly. Students are called to have high creativity, if they have a score higher or equal to the median group (ian median), while students are called to have low creativity, if they have a score less than or below the median (<median) group. The study was conducted in class XI Hospitality 1 by applying the ARIAS learning model, and class XI Hospitality 2 by applying DL. The study found that: (1) students who studied using the ARIAS learning model obtained significantly higher cognitive, affective and psychomotor learning outcomes than students who studied using DL; (2) students who have high creativity, obtain significantly higher cognitive, affective and psychomotor learning outcomes than students who have low creativity; and (3) the relationship between the use of learning models and learning outcomes in continental food processing is influenced by student creativity.